A Flexible Virtual Inertia and Damping Control Strategy for Virtual Synchronous Generator for Effective Utilization of Energy Storage - Utkarsha P.; Naidu N.K.S.; Sivaprasad B.; Singh K.A. (My University, 2025)
This paper presents a flexible virtual inertia and damping control strategy for a virtual synchronous generator (VSG) for the effective utilization of energy storage. Due to their low inertia and low kinetic energy, power electronics-based renewable energy sources are becoming more and more prevalent, which poses major dependability issues for the grid. However, the typical synchronous generator has the ability to adjust to changes in the grid frequency and voltage thanks to load frequency management and an automatic voltage regulator. So, emulating the synchronous machine characteristics in the power electronics-based converter system increases the stability of the grid and further increases the renewable energy penetration in the grid. However, VSG power and frequency oscillates when a sudden disturbance in the power demand occurs in the distributed generation system. This article focuses on minimizing the frequency oscillations as well as power oscillations of VSG during transient conditions or disturbances. Initially, the impact of varying inertia and damping on the active power control loop of VSG is investigated. In addition, the parameters of the VSG are designed in order to minimize the requirement of discharge/charge from the energy storage. So, in this paper, a control strategy with flexible virtual inertia and damping coefficient is designed for optimizing the energy storage unit to support frequency stability. The proposed control method is verified in the developed experimental prototype. In addition, proposed control algorithm is compared with the currently available adaptive control approaches like adaptive inertia control (adaptive $J$ control) and alternating inertia and damping (alternating $J$ and $D_{P}$ control) based VSG and observed that the energy storage requirement and the oscillations in the active power and frequency are minimum in the proposed control method as compared to the other two methods. © 2013 IEEE.